DNA barcodes in identification of some species of hawkmoths (Lepidoptera: Sphingidae) - Trang, Le Quynh; Lien, Vu Van; Viet Thanh, Tran Thi (Academia Journal of Biology, 2022)
The use of DNA barcodes is a molecular method commonly used for the identification of specimens that are difficult to pinpoint accurately by traditional morphological methods. DNA barcoding uses standard short genomic regions that are universally present in target lineages and has sufficient sequence variation to identify species in the genus. The hawkmoth genus Cechetra (Zolotuhin & Ryabov, 2012) was proposed for a group of morphologically similar, stripe-patterned species. Based on the seven specimens of the three species of Cechetra genus collected from the Central of Vietnam, we used morphological analysis to initially identified their scientific name of Cechetra lineosa (Walker, 1856) for 04 specimens (LB_F01, LB_G01, LB_H01 and LK_G05); 02 specimens (MK_H04 and MK_B07) were identified with the scientific name of Cechetra minor (Butler, 1875) and 01 specimen (SG_D7) with scientific name Cechetra subangustata (Rothschild, 1920). Then, the COI (Cytochrome C oxidase I) sequence was used for molecular analysis. Total DNA was extracted from the legs of specimens, COI with over 600 bp in length from each specimen was amplified by PCR reactions. The PCR products are hence purified and sequenced. COI gene cloning results showed a very high level of genetic similarity (over 99%) and 7 specimens are of the genus Cechetra, Sphingidae family. For three homomorphic species belonging to the genus Cechetra Zolotuhin & Ryabov, 2012 including Cechetra lineosa (Walker, 1856); Cechetra minor (Butler, 1875) and Cechetra subangustata (Rothschild, 1920). The studied sequences have been added to the current database at GenBank (NCBI) with accession numbers MT994230, MT994231, MT994232, MT994233, MT994234, MT994235, and MT994236.